GRIK phosphorylates and activates KIN10 which also promotes its degradation - Sun, Jing; Liu, Hui; Blanford, Jantana K.; Cai, Yingqi; Zhai, Zhiyang; Shanklin, John (Frontiers in Plant Science, 2024)
The sensor kinase Sucrose Non-fermenting-1-Related Kinase 1 (SnRK1) plays a central role in energy and metabolic homeostasis. KIN10 is a major catalytic (a) kinase subunit of SnRK1 that is regulated by transcription, posttranslational modification, targeted protein degradation, and its subcellular localization. Kinase 1 and2 (GRIK1 and2) are immediate upstream kinases of KIN10. In the transient protein expression assays carried out in Nicotiana benthamiana (N. benthamiana) leaves, GRIK1 not only phosphorylates KIN10 but also simultaneously initiates its degradation. Posttranslational GRIK-mediated KIN10 degradation is dependent on both GRIK kinase activity and phosphorylation of the KIN10 T-loop. KIN10 proteins are significantly enriched in the grik1-1 grik2-1 double mutant, consistent with the transient assays in N. benthamiana. Interestingly, among the enriched KIN10 proteins from grik1-1 grik2-1, two isoforms of KIN10 putatively derived by alternative splicing have been identified, including a longer isoform which is barely detectable in wild-type plants.